Preemption contests between groups - Stefano Barbieri; Kai A. Konrad; David A. Malueg (The RAND Journal of Economics, 2020)
We consider a preemption game between competing groups; firms lobbying individually for their groups' interests provide an empirical example. Among symmetric groups, the first firm to take action bears an (unobserved) cost and wins the prize on behalf of its group. In equilibrium, the firm with the lowest cost takes action, but with delay. More competition and a smaller ratio of costs to benefits reduce delay. Firms in larger groups wait longer, but group action can occur earlier, as the probability of a low-cost firm is higher. Asymmetries in group size or strength of externalities also~matter.
Keywords: 330